Predictors of Post-Operative Acute Kidney Injury in relation with N-Terminal Pro-B-Type Natriuretic Peptide Level among Patients Undergoing Mitral Valve Replacement (Journal of Current and Advance Medical Research, 2021)
Background: The N-terminal Pro-B-type natriuretic peptide (NT-proBNP) level can be utilized as post-operative prediction models suring cardiac surgery.Objective: The objective was to find out the predictors of post-operative acute kidney injury in relation with N-Terminal Pro-B-Type natriuretic peptide level among mitral valve replacement patients.Methodology: This cross-sectional study was conducted in the Department of Cardiac Surgery at National Institute of Cardiovascular Diseases, Dhaka, Bangladesh from January 2018 to December 2019. Patients with the age of more than or equal to 18 years with both sexes who were underwent mitral valve replacement were selected as study population. Patients were divided into two groups based on pre-operative NT-proBNP level. Post-operatively patients were observed on the basis of post-operative serum creatinine.Results: A total number of 100 patients were recruited for this study of which 50 cases were in group A and the rest of 50 cases were in the group B. Elevated NT-proBNP was the most powerful and independent pre-operative variable in predicting post-operative AKI development (OR 0.999, 95% CI 0.998-1.00) Conclusion: In conclusion elevated NT-proBNP is the most powerful and independent pre-operative variable in predicting post-operative acute kidney injury.Journal of Current and Advance Medical Research, July 2021;8(2):85-89